1999
DOI: 10.1121/1.427777
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition in phonological priming: Lexical or strategic effects?

Abstract: Facilitatory (speeded) and inhibitory (slowed) response times are found in phonological priming experiments, in which the amount of word-initial phoneme overlap between a prime and target is varied (e.g., mark–must). While facilitation appears to be strategic, there is debate as to the nature of the inhibitory priming found when high-overlap prime-target pairs are used (e.g., musk–must). Some researchers propose that this inhibitory priming is due to lexical competition between simultaneously activated candida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…There is also reason to believe that phonemic similarities between primes and targets could affect latency to pronounce. The idea has intuitive appeal but is also supported by research on auditory perception (Shoaf & Pitt, 1998). Specifically, Shoaf and Pitt have shown that latencies to pronounce words are faster when they are preceded by word primes that have similar sounds in the first or second syllables, but longer when the third syllables are similar.…”
Section: Discussionmentioning
confidence: 95%
“…There is also reason to believe that phonemic similarities between primes and targets could affect latency to pronounce. The idea has intuitive appeal but is also supported by research on auditory perception (Shoaf & Pitt, 1998). Specifically, Shoaf and Pitt have shown that latencies to pronounce words are faster when they are preceded by word primes that have similar sounds in the first or second syllables, but longer when the third syllables are similar.…”
Section: Discussionmentioning
confidence: 95%